Intervención de enfermería y su influencia en la calidad de vida de los adultos mayores en el Centro Diurno Geriátrico del Cantón Montalvo periodo junio – octubre 2023 - Almeida Montoya, Nathalia Stephania (2023)
Aging affects not only individuals but also populations, which is called population aging. This is due to the increase in the relative importance of the group of elderly people and the decrease in the percentage of minors due to the decrease in the birth rate. The quality of life is the appreciation in which each individual values their position in life, considering the culture and value system in which they operate, as well as their aspired goals, expectations and standards. The quality of life in the elderly is an abstract concept in which multiple factors that affect this population group are developed. In this study, it was evaluated from various perspectives such as the economy, health, psychological and social problems that lead to depression in the elderly, in addition, caring is helping to be responsible for what may happen to the geriatric population. Nursing interventions generate positive effects for the elderly cared for, but also have positive effects for the person in charge of caring for the elderly patient, significantly reducing the burden of caring for an elderly patient, in addition, the nurse establishes goals and commitments to improve family functionality and thus avoid emotional disturbances, applying and sharing knowledge that provides the caregiver with security, confidence and optimal quality of life.